European Law in Decisions of the Constitutional Court of the Slovak Republic - Peter Rohaľ (Societas et Iurisprudentia, 2017)
Since the accession of the Slovak Republic to the European Union, the European law should become an integral part of the Slovak legal order. This fact led to our decision to examine the decision-making activity of the Constitutional Court of the Slovak Republic in terms of the impact of the European Union law. The paper analyses the activities and selected decisions of the Constitutional Court of the Slovak Republic, summarizing in its summary how the Constitutional Court of the Slovak Republic is coping with them. Finally, we draw our attention to the current proposal which will be the subject of the decision of the Constitutional Court of the Slovak Republic.